Pemanfaatan Ekstrak Buah Senduduk (Melastoma malabathricum L.) sebagai Alternatif Indikator Alami Titrasi Asam Basa dan Implementasinya dalam Praktikum di Sekolah - Riri Ramadhani; Zona Octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
Abstract This research aimed to know which ones produce the solvent a clear color change, precision and accuracy of its use, and can be used as natural indicator a substitute for synthesis indicator. Extraction method used was maceration for 24 hours with solvent of aquadest and ethanol 96% plus 1% concentrated HCl. Determination of pH trajectory using the analysis of color change in the solution of buffer and change the wavelength by UV-Vis spectrophotometer. The feasibility of natural indicator as alternatively substitution of synthesis indicator was assessed through a questionnaire by high school teachers Pekanbaru. Results showed that the trajectory of pH indicator natural from 3.92 to 4.91, the resulting color change was very stark contrast, the pink-purple, precision level of 0.251 and accuracy of 2.58%. Percentage of questionnaires showed a very clear titration discoloration of 85.71%, discoloration of natural indicator titration than synthetic was very clear 85.71%, security of natural indicator for environments was very secure 71.43%, the ratio of security with synthesis indicator was very secure 85.71%, its use as a determinant endpoint can greatly 85.71% , its comparison with the synthesis of 71,43% clear in determining the endpoint. Keywords: Senduduk Fruit (Melastoma malabathricum L.), anthocyanin, maceration, indicators ,acid-basetitration.